Religious life in the late Soviet Union - Martin, Barbara; Beli︠a︡kova, Nadezhda Alekseevna (BASEES/ Routledge series on Russian and east European studies, 2023)
Change of ritual practice under communism : the case of the Russian Orthodox Church in Soviet Ukraine in the late 1950s- early 1970s / Natalia Shlikhta -- The erosion of tradition : life cycle rites among the Orthodox in the Prikam'e Region (1950s-1980s) / Svetlana Riazanova -- The Rybnitser Rebbe and Underground Jewish religious life in the Soviet town of Rybnitsa (1960s-1970s) / Maria Kaspina -- Funeral and memorial rites of Moscow Muslims in the 1960s-1980s / Islam Zaripov and Marat Safarov -- The boundaries of legality as an approach to the study of Soviet religious policy : the case of evangelical Christians-Baptists / Johannes Dyck -- Trying to leave the religious underground : registration of Catholic communities in late Soviet Kazakhstan / Jerzy Rohozinski -- The activism of Soviet Pentecostals in the 1960s-1980s / Vera Kliueva -- Gender specificity of protest activism in unregistered groups of evangelical Christians-Baptists in the late Soviet Union / Nadezhda Beliakova -- A Christian feminism in the USSR? : a historical overview of the religious women's club "Mariia" (1980-1982) / Anna Sidorevich -- Startsy, samizdat and underground seminars : the religious life of young Russian Orthodox converts in the 1970s-1980s / Barbara Martin -- Anatolii Vaneev's circle as a phenomenon of informal church community in Leningrad in the 1970s-1980s / Anna Lepekina -- Longing for Truth, morality, and enchantment : late Soviet spiritual searches and journeys to Islam, 1970s-1980s / Eva Rogaar -- The entry of Indian spiritual movements into the cultural space of Soviet Latvia in the 1970s-80s / Solveiga Krumina-Konkova -- Astrological samizdat in the context of (post-)Soviet esoteric culture / Anna Tessman.